Bequeathing a World: Ecological Inheritance, Generational Conflict, and Dispossession. Issue 2 (1st September 2022) - Weston, Kath
Abstract: In recent debates about climate change, a transmission model of ecological inheritance has apportioned responsibility for ecological damage to generations portrayed as locked in conflict, while depicting Earth as a worldly possession capable of being assigned to a set of heirs. With a focus on North America, this article examines assumptions about ownership, possession, dispositional authority, and succession embedded in the trope of bequeathing an ecologically compromised world to a receiving generation that worries it might be the last. Many of these assumptions create exclusions for those who already apprehend themselves as dispossessed. Indigenous conceptions of responsibility, temporality, and place suggest ways to begin to decolonise the rhetoric of ecological inheritance, allowing humans to inhabit the everyday under signs other than extinction, regardless of how things turn out.